2020
DOI: 10.1016/j.matt.2020.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Organic Frameworks for Macromolecular Recognition and Separation

Abstract: Selective molecular adsorption using metal-organic frameworks (MOFs) has been firmly established as an effective technique in modern separation science. However, polymer insertion into MOFs remains inadequately investigated, probably owing to the large conformational disadvantages commonly associated with spontaneous intercalation processes. Meanwhile, it has been demonstrated that in situ formation of polymers is possible in well-designed nanochannels of MOFs. Being able to take full advantage of the polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…Most recently, this polymer insertion phenomenon has been employed to discriminate between different polymer structures. [44][45][46][47][48] In this manner, MOFs recognize minute differences in polymer architectures upon an insertion event, thus allowing precise polymer separation. 47,48 However, a full understanding of the polymer insertion mechanism remains incomplete despite such prospective applications in the realm of materials science.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, this polymer insertion phenomenon has been employed to discriminate between different polymer structures. [44][45][46][47][48] In this manner, MOFs recognize minute differences in polymer architectures upon an insertion event, thus allowing precise polymer separation. 47,48 However, a full understanding of the polymer insertion mechanism remains incomplete despite such prospective applications in the realm of materials science.…”
Section: Introductionmentioning
confidence: 99%
“…The main pore size of ZIF‐8(NH 3 ⋅ H 2 O) was 0.96 nm, the HPAM‐2 was very hard to adsorb into the pore size for its high molecular weight, which indicating that the insertion kinetics method established by Uemura [32,33] is not suitable for our study. Therefore, Thomas model was used to study the dynamic adsorption.…”
Section: Resultsmentioning
confidence: 98%
“…MOFs have attracted considerable interest owing to their potential as gas storage and separation media [10] . Recently, it has been shown that MOF nanopores can also accommodate various polymers, [11] facilitating the precise recognition and separation of macromolecules [12, 13] . However, previously reported examples of MOF‐based polymer separation have not demonstrated the capacity for large‐scale operation via practical gram‐scale laboratory work‐ups.…”
Section: Figurementioning
confidence: 99%
“…[10] Recently, it has been shown that MOF nanopores can also accommodate various polymers, [11] facilitating the precise recognition and separation of macromolecules. [12,13] However, previously reported examples of MOF-based polymer separation have not demonstrated the capacity for large-scale operation via practical gram-scale laboratory work-ups. Therefore, despite the demand for the implementation of such methods in practical synthetic workflows, addressing both large-scale and precise discrimination of polymer architecture remains challenging.…”
mentioning
confidence: 99%